A Comparative study of native and non-native teachers’ scaffolding techniques in SLA at an early age - Rámila Díaz, Noemi (Estudios Ingleses de la Universidad Complutense, 2009)
The aim of this paper is to analyse the different scaffolding techniques of native and non-native teachers of English in a second language acquisition context with very young students. For that purpose, a new taxonomy of scaffolding techniques was created to tackle the early age of the students, focusing on the form of the teacher’ s utterances and not on the pragmatic function. The data come from the UAM-Corpus and consist of four classes with six-year-old children at a similar level of immersion, two of two native teachers and two of two non-native teachers. For this purpose, the following taxonomies have been taken into account: Lyster and Ranta (1997), Richards and Lockhart (1994), Sinclair and Coulthard (1975) Llinares-García (2005) and Romero-Trillo and Llinares-García (2001). My purpose is to show that depending on the group of teachers, the scaffolding technique used would be different. The results show that native teachers rely more on elaborating their language, whereas non-native teachers rely on eliciting.